2019
DOI: 10.1108/mrr-02-2019-0054
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ISO 26000 social responsibility standard adoption on firm financial performance

Abstract: Purpose The purpose of this paper is to investigate the relationship between the ISO 26000 (global corporate social responsibility standard) adoption and financial performance. The current study aims to explore whether ISO 26000 social responsibility standard adoption has an impact on financial performance. Design/methodology/approach The study is based on a sample consisting of French companies listed on the CAC-All-Tradable index for the period 2010-2017. This study is motivated by using panel data estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 83 publications
4
68
2
4
Order By: Relevance
“…It is noticeable that there is a high divergence in CSR levels across the firms in our sample as the minimum is 7.251 and the maximum 92.66, notably close to the study of Salhi et al (2019) who found that CSR activities in French firms spans from a minimum of 6.852 to a maximum of 90.332. Over the period 2007–2018, the average FP variable is 1.65 considerably lower than the mean value reported by Chakroun et al (2019), 5.628. This difference can be explained by the fact of the difference in the period of study 2010–2017.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…It is noticeable that there is a high divergence in CSR levels across the firms in our sample as the minimum is 7.251 and the maximum 92.66, notably close to the study of Salhi et al (2019) who found that CSR activities in French firms spans from a minimum of 6.852 to a maximum of 90.332. Over the period 2007–2018, the average FP variable is 1.65 considerably lower than the mean value reported by Chakroun et al (2019), 5.628. This difference can be explained by the fact of the difference in the period of study 2010–2017.…”
Section: Resultsmentioning
confidence: 59%
“…These factors are firm size and firm leverage. Firm size is measured by taking the natural log of total assets; one of the most frequently used measures for firm size (Salhi et al , 2019; Kachouri et al , 2020; Chakroun et al , 2019). As larger firms possess more resources, they are thus more likely to invest in CSR (Acabado et al , 2020; Godos-Díez et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the literature, we included two control variables that are expected to influence CSR, namely, firm size and leverage (D'Amato and Falivena, 2020; Ongsakul et al, 2019;Dwekat et al, 2020;Mouakhar et al, 2020). Firm size was measured by taking the natural log of total assets, one of the most frequently used measures for firm size (Salhi et al, 2019;Kachouri et al, 2020;Chakroun et al, 2019) as larger firms possess more resources and are thus more likely to invest in CSR (Acabado et al, 2020;Godos-Díez et al, 2020). Also, they are likely to issue more voluntary disclosures because they receive more attention from the public and thus are under higher pressure to disclose more information about CSR activities to legitimize their activities (Gavana et al, 2017;El-Bassiouny and Letmathe, 2018;Orazalin, 2019).…”
Section: Control Variablesmentioning
confidence: 99%
“…The reasons for the success of CSR activities in the form of improved profitability and increased value on the market are most often indicated in the improvement of the image, competitive position, and positive response from customers and stock market investors [77][78][79][80]. Publications emphasize that in order to achieve such an effect, CSR activities should be properly directed and constitute a relatively coherent system, and the environment should be informed about CSR activities [81][82][83].…”
Section: Csr In the Energy Industrymentioning
confidence: 99%